2017
DOI: 10.1007/s11657-017-0314-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of cone beam computed tomography in identifying postmenopausal women with osteoporosis

Abstract: Quantitative CBCT indices may help dentists to screen for women with low spinal and femoral bone mineral density so that they can refer postmenopausal women for bone densitometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 24 publications
1
38
0
5
Order By: Relevance
“…Mostafa et al [9] showed that CT mental index, CT mandibular index and CT cortical index scores were significant differences between the control and osteoporotic groups. Brasileiro et al [10] indicated that the mean values of CT index and CT mandibular index were lower in the osteoporosis group than in osteopenia and normal patients. Therefore, we consider that cortical bone density of mandible with CBCT should be utilized as predict factor of osteoporosis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Mostafa et al [9] showed that CT mental index, CT mandibular index and CT cortical index scores were significant differences between the control and osteoporotic groups. Brasileiro et al [10] indicated that the mean values of CT index and CT mandibular index were lower in the osteoporosis group than in osteopenia and normal patients. Therefore, we consider that cortical bone density of mandible with CBCT should be utilized as predict factor of osteoporosis.…”
Section: Discussionmentioning
confidence: 97%
“…[11] In recent years, 3D image datasets obtained from CBCT have been applied to investigating the potential osteoporosis prediction. [8][9][10][11][12] Therefore, we investigated the changes of mandibular cortical bone with age using CBCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estudios que evaluaron la estructura ósea trabecular de los maxilares en TCHC, no revelaron grandes cambios que podrían identificarse como osteoporosis, arrojando datos más significativos de osteoporosis al analizar y evaluar el trabeculado óseo de la 2da vértebra cervical a nivel del odontoides (50), es así que mediante la tomografía y la resonancia magnética, se podría evaluar la estructura del hueso trabecular, midiendo el volumen, el espaciado y la conectividad, los estudios son prometedores; pero los costos y la complejidad de estos métodos, serían una limitante del uso diario en la práctica clínica (50,51).…”
Section: • Corteza Leve a Moderadamente Erosionada (C2)unclassified
“…However, high cost of machine constructing, radiation exposure and unavailability prevent DXA as an ideal screening tool among clinics or hospitals at countryside. Quantitative computed tomography (QCT) different from DXA has advantages of giving precise volumetric mineral density of separate trabecular and cortical bone at the interested regions of any size or shapes . However, limitations of QCT similar to DXA are doomed to restrict its utility for osteoporosis screening.…”
Section: Introductionmentioning
confidence: 99%